2019
DOI: 10.7150/jca.28659
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab Plus Paclitaxel and Cisplatin as a 1st-Line Treatment for Esophageal Cancer: Long Term Follow-up of a Phase II Study

Abstract: The effect of anti-epidermal growth factor receptor targeted treatment in esophageal squamous cell carcinoma (ESCC) is still unclear. We conducted a prospective phase II study of paclitaxel, cisplatin, and nimotuzumab (TPN) as a first-line treatment for unresectable or metastatic ESCC and the objective response rate was 51.8%. Here, we report the long-term follow-up results of the initial trial. Fifty-nine patients were enrolled from Mar 2011 to Apr 2013 and were treated with the TPN regimen. Palliative sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Given the high incidence of severe gastrointestinal toxicity, leukopenia, radiation dermatitis and radiation pneumonitis caused by paclitaxel chemotherapy, the screening for sensitive populations is particularly important. 46 , 47 Our analysis shows that CSMD1 mutation status can be used as a biomarker to screen ESCA patients sensitive to paclitaxel chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Given the high incidence of severe gastrointestinal toxicity, leukopenia, radiation dermatitis and radiation pneumonitis caused by paclitaxel chemotherapy, the screening for sensitive populations is particularly important. 46 , 47 Our analysis shows that CSMD1 mutation status can be used as a biomarker to screen ESCA patients sensitive to paclitaxel chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…EGFR has been shown to be up-regulated in 30-90% of esophageal cancer patients 9 and 27%-64% of gastric cancer patients, 10 respectively. However, all the clinical trials of monoclonal antibody and tyrosine kinase inhibitors targeted to EGFR did not gave us the positive outcome, such as cetuximab, 11 , 12 panitumumab, 13 nimotuzumab, 14 gefitinib and erlotinib. 15 , 16 Trastuzumab and ramulizumab have clear efficacy in adenocarcinoma, but lack of clinical evidence in esophageal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have concluded that cetuximab is not beneficial in patients with low EGFR expression ( 32 ), and whether the high expression of EGFR is associated with larger tumors or T stage 3-4 is the reason why cetuximab is more effective can be further confirmed. In addition, sex was an independent predictor of OS in EC patients ( 33 ). The sex subgroup results showed that cetuximab combined with CRT was relatively superior to the control in female EC patients but inferior to the control in male EC patients.…”
Section: Discussionmentioning
confidence: 99%